Pelayanan Farmasi untuk Daerah Tertinggal, Terdepan, dan Terluar (3T) Terkait Program Penyakit HIV Berdasarkan Integrasi Model Pemberi Layanan yang Terdiferensiasi (PLD): Sebuah Tinjauan Sistematis - Fransiskus Samuel Renaldi; Khrisna Pangeran (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Differentiated Service Delivery (DSD) has been proposed to improve HIV treatment continuity in remote areas; however, its success depends on the integration of systemic supports. Objective: This review synthesizes evidence on the effectiveness of community-based DSD models and the determinants of their success in underdeveloped, frontier, and outermost (3T) areas, particularly concerning supply chain resilience, quality assurance, and aligned governance and financing. Methods: A systematic review with narrative synthesis was conducted following PRISMA guidelines. Literature searches were performed in PubMed, Scopus, Web of Science, and grey literature repositories (2010–2025). Out of 1,520 records, 32 studies met the inclusion criteria. Results: Community-based DSD models (ART groups, MMD) were effective in improving adherence, retention, and reducing visit burden. This success was strongly determined by: (1) ARV supply chain stability (minimal stock-out days, synchronization with MMD schedules); (2) quality assurance in storage–distribution (temperature control, FEFO); and (3) aligned governance and financing (pharmacist roles, community health worker incentives, last-mile funding). Qualitative findings identified service proximity, confidentiality, and logistical reliability as key facilitators. Conclusion: DSD is a systemic intervention whose effectiveness hinges on multidimensional readiness. Strengthening HIV pharmaceutical services in 3T areas requires an integrated approach that simultaneously builds supply resilience, service quality, and adaptive governance. This review proposes operational indicators and a phased implementation roadmap for contextual adaptation.